2022
DOI: 10.1038/s41419-022-05510-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune microenvironment and immunotherapy efficacy in BRAF mutation non-small-cell lung cancer

Abstract: Previous small-size studies reported BRAF-mutated NSCLC patients have comparable sensitivity to immune checkpoint inhibitors (ICIs). However, how BRAF mutation affects the tumor immune microenvironment (TIME) is unknown. We performed Nanostring-panel RNA sequencing to evaluate TIME in 57 BRAF mutated and wild-type (WT) NSCLC specimens (cohort A). The efficacy of ICI monotherapy or combined therapies was determined in 417 patients with WT and BRAF mutated NSCLC (cohort B). We found that BRAF-mutant tumors had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…This efficacy benefit with immunochemotherapy was not observed in later lines. Another retrospective study showed similar efficacy with immunotherapy-based treatments in patients with advanced NSCLC with or without BRAF mutations; median PFS was 8.4 months in both patient populations 83 . In the BRAF cohort, median PFS was similar for V600E and non-600E mutations (10.0 versus 8.0 months).…”
Section: Treatment Landscapementioning
confidence: 87%
See 1 more Smart Citation
“…This efficacy benefit with immunochemotherapy was not observed in later lines. Another retrospective study showed similar efficacy with immunotherapy-based treatments in patients with advanced NSCLC with or without BRAF mutations; median PFS was 8.4 months in both patient populations 83 . In the BRAF cohort, median PFS was similar for V600E and non-600E mutations (10.0 versus 8.0 months).…”
Section: Treatment Landscapementioning
confidence: 87%
“…Median PFS was longer in the first line than in subsequent treatment lines in patients with WT (12.8 versus 5.6 months) and BRAF-mutant (11.2 versus 4.0 months) NSCLC. These studies suggest that immunotherapy-based treatments are an option for patients with BRAF V600E -mutant advanced NSCLC 82 , 83 .…”
Section: Treatment Landscapementioning
confidence: 98%
“…However, Li et al reported no differences of PD‐L1 expression between BRAF mutations and wild‐type BRAF groups and between two BRAF genotypes. Furthermore, patients with advanced NSCLC with V600E and non‐V600E BRAF mutations had similar OS 25 …”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, patients with advanced NSCLC with V600E and non‐V600E BRAF mutations had similar OS. 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation